Numerical Simulation of Rotor in Hover and Forward Flight - Zhao Qinghe (MATEC Web of Conferences, 2018)
The flow around rotor is numerical simulated in hover and forward flight based on multi-structured grid. In hover the flow field can be transformed into a steady-state flow field in the rotating coordinate system. The experimental data of Caradonna and Tung rotor is used to verify the numerical simulation result. The numerical results compare well with the experimental data for both non-lifting and lifting cases. Non-lifting forward flight is simulated and the prediction capabilities have been validated through the ONERA two-blade rotor. The pressure distributions of different positions under different azimuth angles are compared, which is in good agreement with the experimental data. There is unsteady shock wave when forward flight. Dual-time method is used to obtain unsteady flow field with rigid moving grid in the inertial system.